2020
DOI: 10.1097/md.0000000000021186
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of microRNA profiles and identification of microRNA-mRNA network and biological markers in intracranial aneurysm

Abstract: Intracranial aneurysm (IA) is a kind of cerebrovascular disorder, which may result in the subarachnoid hemorrhage with high lethality and disability. The purpose of this study was to reveal the pathogenesis and identify novel biomarkers in IA. We processed the raw microRNA (miRNA) expression profile data of IA obtained from Gene Expression Omnibus. Then weighted correlation network analysis was performed to identify the hub miRNAs in IA. Target genes of hub miRNAs were predicted using multiR package… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…23 , 24 Analysis of the expression of VEGF, Bcl-2, and MT1-MMP in this research revealed that miR-423-5p was a good predictor of HFmrEF, which could accurately indicate an improved cardiac function in those patients following cardiac rehabilitation treatment. Combined with previous studies, our data suggest that miR-423-5p may induce cardiomyocyte apoptosis by regulating the PI3k/AKT pathway 25 and inhibiting O-type N -acetylglucosaminyltransferase (OGT). 26 Meanwhile, cardiac rehabilitation may improve cardiac function, promote physiological structural changes in the heart, and inhibit cardiac physiological remodeling 27 by regulating endothelial progenitor cells via miR-423-5p.…”
Section: Discussionsupporting
confidence: 77%
“…23 , 24 Analysis of the expression of VEGF, Bcl-2, and MT1-MMP in this research revealed that miR-423-5p was a good predictor of HFmrEF, which could accurately indicate an improved cardiac function in those patients following cardiac rehabilitation treatment. Combined with previous studies, our data suggest that miR-423-5p may induce cardiomyocyte apoptosis by regulating the PI3k/AKT pathway 25 and inhibiting O-type N -acetylglucosaminyltransferase (OGT). 26 Meanwhile, cardiac rehabilitation may improve cardiac function, promote physiological structural changes in the heart, and inhibit cardiac physiological remodeling 27 by regulating endothelial progenitor cells via miR-423-5p.…”
Section: Discussionsupporting
confidence: 77%
“…A primary limitation in these studies remains the small sample sizes within the GEO datasets explored. However, it is noteworthy that some studies have validated their findings in distinct GEO datasets [ 101 , 102 , 103 ].…”
Section: Resultsmentioning
confidence: 97%
“…Despite the small study size, this independent analysis can be used to confirm that miR-424-5p is a biomarker for the beginning of CVD. Others also reported miR-424-5p to be a biological marker of intracranial aneurism [ 50 ] or predictor of risk of fatal myocardial infarction whilst combined with Framingham score [ 51 ].…”
Section: Discussionmentioning
confidence: 99%